Pengaruh Motivasi, Disiplin Kerja dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Bank BTN Kantor Cabang Balikpapan - Athifa Zahra; Syahril Hasan; Tutik Yuliani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine the influence of motivation variables, work discipline and work environment on job satisfaction of Bank BTN Kantor Cabang Balikpapan employees. This research uses a quantitative descriptive approach. The population of this study was 133 employees of Bank BTN Kantor Cabang Balikpapan. The sampling technique in this research used purposive sampling, totaling 59 permanent employees. Data collection was carried out by literature study, interviews and distributing questionnaires, processing data using SmartPLS to test the validity and reliability of the instrument. An R-Square value of 0.705 indicates a good work model, with job satisfaction influenced by 70.5% by motivation variables, work discipline and work environment. The research results show that work motivation and discipline have a positive and significant influence on the job satisfaction of Bank BTN Kantor Cabang Balikpapan employees, while the work environment has no effect and is not significant on the job satisfaction of Bank BTN Kantor Cabang Balikpapan employees. It is recommended to increase the feeling of comfort in the work environment, maintain employee discipline and increase motivation to build employee enthusiasm in carrying out their work, as well as involving additional variables such as compensation, leadership and loyalty in further research.